Pelatihan, Pendampingan Perizinan Berusaha Produk UMKM melalui Peran Mahasiswa Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung - Binti Nur Asiyah (Inspirasi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This paper aims to conduct training on business licensing assistance for MSME products through the role of Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung students. MSMEs are widespread in the community, but the ownership of a Business Permit Number (NIB) is still low, so it was initiated by the Minister of BKPM and the Minister of Cooperatives and MSMEs related to the oss.go.id digital platform which makes it easy for MSMEs to register their business. However, as the ability and knowledge of SMEs to manage business license numbers are still limited, the role of students is needed to take part in assisting SMEs to have a Business Permit Number. This service is written with a service learning approach that provides easy services for training participants so that they have the knowledge and ability to access new platforms for business licensing. The result of this service is that training on business licensing assistance for MSME products has been carried out through the role of Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung students on October 16, 2021 online through the media zoom. The training participants were 68 participants, and the training resource persons were East Java Transfumi Guard Volunteers, Tulungagung Transfumi Guard Volunteers as well as Postgraduate Lecturers and FEBI Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, as well as the Tulungagung PLUT Institutional Division. Among the materials presented were (1) The role of students in encouraging the MSME community in managing business legality, 2) Introduction of the OSS system, 3) Licensing of low, medium, medium, high, high risk micro businesses.